Karagenin sebagai Model Inflamasi pada Kulit Punggung Mencit: Gambaran Makroskopik dan Histopatologis (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
This study aims to create a model of dorsal skin inflammation in mice using carrageenan with various concentrations. Forty-five female Swiss mice with the aged of 8 weeks were used in this study. These mice were divided into three groups of 15. Group I, II and III was given subcutaneous injection of 1%, 2% and 4% carrageenan respectively on the dorsum. Carrageenan was dissolved in 0.9% buffer saline with 0.1 mL volume injection. Prior to carrageenan injection, dorsal skin-fold thickness was measured using calipers and then was repeated every hour up to 6 hours. At the end of the sixth hour of measuring skin-fold thickness, animal was sacrificed, the dorsal skin was excised and then was fixed in 10% buffer formalin for histopathological examination. Data from skin-fold thickness measurement was analyzed using Two Ways Anova followed by Tukey HSD test. Results of this study demonstrate that there was a significant difference in skin-fold thickness between treatment groups (p<0.05). Sub cutaneous injection of 1%, 2% and 4% carrageenan resulted in increasing skin-fold thickness approximately 35%, 50% and 61% at the one-hour post carrageenan injection respectively (p<0.05). Skin-fold thickness gradually decreased at the second to the sixth hour after carrageenan injection. Histopathological examination shows mild and moderate dermal inflammation in the group given 1% and 2% carrageenan respectively. Severe dermal and panniculus inflammation was found in the group given 4% carrageenan. To conclude, carrageenan could be used to induce inflammation in back skin of mice.